Recruitment of Young Bull Trout into the Metolius River and Lake Billy Chinook, Oregon. (7th November 2015) - Ratliff, Don; Spateholts, Robert; Hill, Megan; Schulz, Eric
Abstract: The abundance of Bull Trout Salvelinus confluentus in the Metolius River and Lake Billy Chinook, a hydroelectric reservoir, increased dramatically from 1998 to 2004, following implementation of restrictive fishery regulations. However, both adult Bull Trout and kokanee Oncorhynchus nerka (prey) populations have declined in more recent years. We investigated the relationships between Bull Trout spawner densities, emerging fry densities, and numbers of juveniles migrating into the reservoir to determine the potential role of juvenile production in this decline. We hypothesized that age‐1 and older juvenile production is now limited by natal habitat capacity and that excess fry production is lost to density‐dependent mortality. Bull trout redd densities in surveyed spawning reaches ranged from 14 to 39 redds/km during recent years. The estimated abundance of emerging Bull Trout fry in monitored spawning reaches has varied from about 1.0–2.5 million annually since 2005, while mean estimated densities of newly emerged fry varied from over 35/m 2 in Roaring Creek during 2005 to less than 1/m 2 in Jefferson Creek during 2009. Fry capture numbers from high versus low escapement broods at the Metolius River downstream trap varied by a factor of four, but capture of age‐1 and age‐2 juveniles did not differ substantially. These findings indicate natal Bull Trout habitats are seeded at spawner densities of 14 redds/km and higher. Fry in excess of natal habitat capacity are probably lost to density‐dependent mortality factors. We estimate natural recruitment of age‐1 and older Bull Trout into Lake Billy Chinook of at least 9 individuals/ha annually since 2001. Recent population bottlenecks limiting adult Bull Trout abundance occurred after juvenile recruits entered the lake and are probably related to prey availability. Received February 23, 2015; accepted July 8, 2015